(untitled) (Applied Biological Research, 2025)
Initial trials on MCF-7 breast carcinoma cells with the crude methanolic extracts of Asparagus racemosus tubers (MAR) and Boerhaevia diffusa leaves (MBD) revealed pro-oestrogenic and anti-oestrogenic activities, respectively. To evaluate their effects on steroidogenic pathway, the present study assessed the modulation of expression of steroidogenic acute regulatory protein (StAR), cytochrome P45011A1 (CYP11AI), and aromatase (CYP19) genes in extract- treated MCF-7 cells. Naringenin, a known CYP450 inhibitor, served as the positive control. Shade-dried plant materials were extracted in methanol, and cytotoxicity was evaluated by MTT assay to determine IC50 values. The IC50 of MAR, MBD and naringenin were 267, 170, and 395 μg mL ̈1, respectively. Cells were treated with IC50, half, and double IC50 doses of the test materials for 96 h, followed by RNA extraction and qRT-PCR analysis using GAPDH as a reference gene. MBD and naringenin significantly downregulated StAR and CYP19, indicating antioestrogenic effects, whereas MAR upregulated CYP1A1 expression, suggesting enhanced steroidogenesis. The findings indicate that A. racemosus promotes oestrogen biosynthesis and may be beneficial in hormone deficiency, while B. diffusa exhibits antioestrogenic and potential anticancer activity in hormone-responsive cancers.